Plankton Diversity of Welang River in the Mount Baung Nature Tourist Park, Pasuruan Regency East Java Province - Nur Patria Kurniawan; Luvi Andari; Liris Lis Komara (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2026)
The Welang River in the Gunung Baung Nature Tourism Park (TWA), Pasuruan, plays a vital role as a source of clean water, irrigation, and ecotourism, but is vulnerable to contamination from upstream areas with dense activity. This water quality degradation requires monitoring, and biological analysis using plankton as a bioindicator is a holistic method due to the sensitivity of these organisms to environmental changes. This study aims to determine the structure and plankton community (phytoplankton and zooplankton) in the Welang River and analyze its ecological condition based on the plankton diversity index. The method used is descriptive quantitative with a purposive sampling technique at three stations. Sampling was conducted using a volume sampler technique and abundance was calculated using a Sedgewick Rafter Counting cell. Data analysis included calculations of abundance, Diversity Index (H'), Evenness (E), Richness (R), and Dominance (D). The results showed that the plankton community as a whole was in the category of moderate diversity, high evenness, and very low dominance. This value indicates that the Welang River waters are in a stable ecological condition and are not heavily polluted. As conclusion, the water quality of the Welang River is stable but shows an early warning of nutrient enrichment from anthropogenic activities, especially from the upstream.